Gel combustion synthesis of zinc oxide nanoparticles - Shah N.N.H.; Misran H.; Razak N.A.A. (Microscopy Society of Malaysia, 2023)
Zinc oxide nanoparticles were successfully synthesized using gel combustion synthesis route. Zinc nitrate was used as oxidant and palm oil derived fatty alcohol (C8 - octyl alcohol) as well as glycerol functioned as organic dispersants and fuel. The materials were directly mixed and heated until combustion creating zinc oxide/carbon composite. The resulting X-ray diffraction patterns of ZnO nanoparticles were well indexed to the hexagonal phase with wurtzite structure. Additional peaks were not detected in XRD patterns suggesting that no other phases were formed during the combustion synthesis. FE-SEM images of the calcined sample using glycerol as fuel exhibited elongated spindle-like shapes consisted of nanoparticles at ca. 100 nm. In addition, EDX analyses showed that peaks of zinc and oxygen existed suggesting that pure zinc oxide was formed successfully using the new gel combustion method. 2019, Microscopy Society of Malaysia. All rights reserved.